The Role of Rare Coding Variants in Parkinson's Disease GWAS Loci - Germer, Elisabeth Luisa; Imhoff, Sophie; Vilariño-Güell, Carles; Kasten, Meike; Seibler, Philip; Brüggemann, Norbert; , International Parkinson’s Disease Genomics Consortium; Klein, Christine; Trinh, Joanne (Frontiers in Neurology, 2019)
Introduction: Genome-wide association studies (GWAS) have identified multiple loci associated with PD risk. The presence of rare variants within these loci that may account for the increased susceptibility requires further investigation. Methods: Using exome sequencing, we performed a comprehensive rare variant screen of genes located within 56 novel PD loci. We first analyzed exomes from 109 subjects in the discovery cohort (85 diagnosed with PD and 24 healthy controls), and filtered for rare coding variants with MAF<0.01 and CADD>15. Further investigation of exome data from a replication cohort of 2,859 European patients with PD (IPDGC) and 24,146 non-Finnish European controls from gnomAD were used for association testing of specific rare variants found in the discovery cohort. Results: Our genetic screening identified 54 potential disease-relevant variants in 71 genes in 109 subjects. Six out of 54 variants were found in two or more patients and were not observed in healthy controls: DNAH1 p.A3639T, STAB1 p.S1089G, ANK2 p.V3634D, ANK2 p.R3906W, SH3GL2 p.G276V, NOD2 p.G908R. Replication in the IPDGC confirmed the association with PD risk for three out of the six identified variants (STAB1 p.S1089G, SH3GL2 p.G276V, and NOD2 p.G908R) (p<10-3). Conclusion: Our study suggests that some of the associations identified in PD risk loci can be ascribed to rare variants with likely functional effects that modify PD risk.